STUDIES ON THE HETEROPTERAN (INSECTA: HETEROPTERA) FAUNA OF AMBA RESERVED FOREST, WESTERN GHATS, MAHARASHTRA - S. R. ALAND,; A. B. MAMLAYYA,; Y. J. KOLI,; D. L. BHARMAL,; G. P. BHAWANE, (The Bioscan, 2010)
For the first time Surveys and collection of bugs in Amba Reserved Forest, Western Ghat, Maharashtra was carried out in 2007-2008. During the study period, 44 species of bugs belonging to 36 genera representing 09 families viz. Pentatomidae, Coreidae, Lygaeidae, Pyrrhochoridae, Gerridae, Nepidae, Belostomatidae, Ranatridae and Rhyparochoridae were recorded. Family Pentatomidae represented maximum 22 species. Data revealed that, the fauna of bugs of study region is rich may be because of variety of food plants, varied ecological conditions and rainfall, temperature and topography.